Hubungan antara Anonimitas dan Moral Disengagement dengan Perilaku Cyberbullying pada Penggemar K-Pop yang Melakukan Fanwar - Khoiriyah, Erfira; Pramono, Ridwan Budi (Jurnal Psikologi Perseptual, 2023)
This study is a quantitative study that aims to determine the relationship between anonymity and moral disengagement with cyberbullying behavior in K-Pop fans who do fanwar. Purposive sampling was used in sampling so that 250 K-Pop fans filled out the cyberbullying scale, anonymity scale, and moral disengagement scale. The results of the analysis show that there is a relationship between anonymity and moral disengagement with cyberbullying behavior in K-pop fans who do fanwar with a correlation coefficient of 0.413 and a p value 0.001 (p 0.01) and an effective contribution of 17%. Anonymity is positively and significantly related to cyberbullying as indicated by a correlation coefficient of 0.271 and a p value of 0.001 (p 0.01). Moral disengagement is positively and significantly related to cyberbullying as indicated by a correlation coefficient of 0.398 and a p value of 0.001 (p 0.01). The results indicate that anonymity and moral disengagement can increase individual participation in cyberbullying behavior. Structural Equation Modeling (SEM) analysis was conducted to assess the strength of aspects. The aspect of "Imbalance Power" in measuring cyberbullying, the aspect of "Lack of Identification" in measuring anonymity, and the aspect of "Moral Justification" in measuring moral disengagement have low loading factors, thus proving less effective in measurement in this research. Penelitian ini merupakan penelitian kuantitatif yang bertujuan untuk mengetahui hubungan antara anonimitas dan moral disengagement dengan perilaku cyberbullying pada penggemar K-Pop yang melakukan fanwar. Purposive sampling digunakan dalam pengambilan sampel sehingga 250 penggemar K-Pop mengisi skala skala cyberbullying, skala anonimitas, dan skala moral disengagement. Hasil analisis menunjukkan bahwa terdapat hubungan anonimitas dan moral disengagement dengan perilaku cyberbullying pada penggemar K-pop yang melakukan fanwar dengan koefisien korelasi 0.413 dan nilai p 0.001 (p 0.01) serta sumbangan efektif sebesar 17%. Anonimitas berhubungan positif yang sangat signifikan dengan cyberbullying ditunjukkan dengan koefisien korelasi 0.271 dan nilai p 0.001 (p 0.01). Moral disengagement berhubungan positif yang sangat signifikan dengan cyberbullying ditunjukkan dengan koefisien korelasi 0.398 dan nilai p 0.001 (p 0.01). Hasil penelitian menunjukkan bahwa anonimitas dan moral disengagement dapat meningkatkan partisipasi individu dalam perilaku cyberbullying. Analisis Structural Equation Modeling (SEM) dilakukan untuk mengukur kekuatan aspek. Aspek “Ketidakseimbangan Kekuatan” dalam mengukur cyberbullying. Aspek “Kurangnya Identifikasi” dalam mengukur anonimitas, dan Aspek “Justifikasi Moral” dalam mengukur moral disengagement memiliki loading factor yang rendah sehingga kurang efektif melakukan pengukuran dalam penelitian ini.